Bantuan Pembuatan Peta Jalan RT 01 RW 12 Perumahan Sebantengan Baru Kelurahan Ungaran Kabupaten Semarang - Ratih Widiastuti (Sekolah Vokasi Universitas Diponegoro, 2023)
The availability of proper roads is one of the important supporting factors to develop rural areas. Some of the broken roads in the area of RT 01 RW 12, Perumahan Sebantengan Baru, Ungaran Region need to be fixed. In order to get funding from the local government, a proper road map is needed as one of the requirements. Due to lack of knowledge, the local authority faced difficulty producing a proper road map. In supporting the agenda of the authority and also practices the knowledge from the university, the community service programme from Civil Infrastructure Engineering and Architectural Design, Department of Civil and Planning, Vocational School, Diponegoro University, assisted producing a proper road map of the broken road in the area of RT 01 RW 12, Perumahan Sebantengan Baru, Ungaran Region.